2013
DOI: 10.1038/aps.2012.153
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of ccl19 gene enhances anti-caries DNA vaccine pCIA-P immunogenicity in mice by increasing dendritic cell migration to secondary lymphoid tissues

Abstract: Aim: To investigate how co-delivery of the gene encoding C-C chemokine affected the systemic immune responses to an anti-caries DNA vaccine pCIA-P in mice. Methods: Plasmid encoding CCL19-GFP fusion protein (pCCL19/GFP) was constructed by inserting murine ccl19 gene into GFPexpressing vector pAcGFP1-N1. Chemotactic effect of the fusion protein on murine dendritic cells (DCs) was assessed in vitro and in vivo using transwell and flow cytometric analysis, respectively. BALB/c mice were administered anti-caries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Although multiple factors influence immunization outcomes, our findings provide one explanation for the failure of CCL19, as an adjuvant, to boost immune response to HIV-1 VLPs in a previous study (54), in which a lower dose (50 mg/mouse) of pCCL19 was used. We (75) and other investigators (40) clearly observed that pCCL19, when delivered at 100 mg/ mouse, had modulating effects in enhancing Ag-specific responses to HIV-1 gp140, HSV-1 gB, and the PAc Ag of Streptococcus mutans. DNA immunization is most commonly used in conjunction with alternative boosting strategies, such as the use of viral vectors or recombinant proteins.…”
Section: Discussionmentioning
confidence: 51%
“…Although multiple factors influence immunization outcomes, our findings provide one explanation for the failure of CCL19, as an adjuvant, to boost immune response to HIV-1 VLPs in a previous study (54), in which a lower dose (50 mg/mouse) of pCCL19 was used. We (75) and other investigators (40) clearly observed that pCCL19, when delivered at 100 mg/ mouse, had modulating effects in enhancing Ag-specific responses to HIV-1 gp140, HSV-1 gB, and the PAc Ag of Streptococcus mutans. DNA immunization is most commonly used in conjunction with alternative boosting strategies, such as the use of viral vectors or recombinant proteins.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, DC-based anticaries vaccines are well developed. 22 The size of the nanoparticle might influence the efficiency of their uptake by DCs. For example, smaller nanoparticles (»20 nm in diameter) are more immunogenic compared with larger nanoparticles (»500 nm in diameter), even after a single immunization.…”
Section: Discussionmentioning
confidence: 99%
“…CCL19, which is secreted by stromal cells in the T-cell area of DLNs, is a high-affinity functional ligand for CCR7. Our previous findings showed that CCL19 is a potent chemoattractant for in vitro-expanded bone marrow-derived DCs, and the specificity was confirmed by CCR7 blockade of mature DCs [20] . In this study, we showed that exogenous overexpression of CCL19 enhanced the recruitment of DCs to DLNs.…”
Section: Discussionmentioning
confidence: 78%
“…Our previous studies showed that a CCL19 DNA plasmid entered the secondary lymphoid tissues and expressed the chemokine there following intramuscular administration. Using a CCL19 plasmid in combination with the anti-caries DNA vaccine pCIA-P, an increased serum PAc-specific IgG level was observed [20] . To date, by virtue of its paramount importance in diverse effects on DC and lymphocyte migration and immune response formation, it has been postulated that CCL19 is an interesting candidate vaccine adjuvant for a number of infectious diseases [19,32,33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation